BALINESE SCRIPT IN TATTOO MEDIA COMMODITY IN DENPASAR BALI - Setiawan, I Nyoman Anom Fajaraditya (ADI Journal on Recent Innovation, 2020)
Tattoos in the realm of Indonesian culture has now entered the realm of the tourism industry. Bali in particular, the tattoo is a promising industry, especially in tourist destinations. The presence of rapid tourism development and support of information technology provides opportunities for the enrichment of works in tattoos. Previous influence of outer style on a tattoo in Bali give the effect of shifting perspective to tattoo phenomenon during this time. Changes also occur in ornaments that penetrate the art or tradition ornaments because previously this is a taboo to do. The first step is to collect the data purposively so that it can be interpreted and described in a qualitative comparative analysis. The existence of commodities makes an indication of commodification in the practice of tattoo Balinese script, and there is the hidden motivation behind it. The meaning that can be extracted in this phenomenon is the symbolization that is understood only by the artist and his collector. This situation is symbiotic with the market changing the value that exists in the object and also emerges a creative effort that impacts on the sustainability of traditional Balinese script.